Alleviation of Heavy Metal Stress in Plants and Remediation of Soil by Rhizosphere Microorganisms - Mishra, Jitendra; Singh, Rachna; Arora, Naveen K. (Frontiers in Microbiology, 2017)
Increasing concentration of heavy metals (HM) due to various anthropogenic activities is a serious problem. Plants are very much affected by HM pollution particularly in contaminated soils. Survival of plants becomes tough and its overall health under HM stress is impaired. Remediation of HM in contaminated soil is done by physical and chemical processes which are costly, time-consuming and non-sustainable. Metal-microbe interaction is an emerging but under-utilized technology that can be exploited to reduce HM stress in plants. Several rhizosphere microorganisms are known to play essential role in the management of HM stresses in plants. They can accumulate, transform or detoxify HM. In general, the benefit from these microbes can have a vast impact on plant’s health. Plant‐microbe associations targeting HM stress may provide another dimension to existing phytoremediation and rhizoremediation uses. In this review, applied aspects and mechanisms of action of heavy metal tolerant (HMT) plant growth promoting (PGP) microbes in ensuring plant survival and growth in contaminated soils is discussed. The use of HMT-PGP microbes and their interaction with plants in remediation of contaminated soil can be the approach for the future. This low input and sustainable biotechnology can be of immense use/importance in reclaiming the HM contaminated soils, thus increasing the quality and yield of such soils.